Periodically corrugated waveguides for slow-wave THz free-electron laser - Hossein Shirvani; Chih-Ying Lien; Yen-Chieh Huang (Physical Review Accelerators and Beams)
We investigate a slow-wave THz free-electron laser consisting of axially or helically corrugated waveguides driven by an annular electron beam. When the device is driven by a 10-mA electron beam at 30 keV, we numerically demonstrated backward-wave oscillation at 0.2212 and 0.2651 THz in axially and helically corrugated waveguides, respectively, without a solenoid field within a submillimeter aperture. We developed a unified theoretical framework for the two types of waveguides and successfully explained the observed backward-wave resonances. In our theory, azimuthal-symmetry breaking in a helically corrugated waveguide couples the synchronous transverse-magnetic radiation mode to a transverse-electric mode, resulting in radiation loss for the oscillation. Therefore, this study concludes superior radiation performance for the axially corrugated waveguide as a slow-wave THz free-electron laser. Furthermore, we show the opportunity of exciting self-started cyclotron resonance maser oscillations at THz frequencies from a helically corrugated waveguide without a solenoid field.